Mammals - Geron, Eric (New York, NY : Children's Press, an imprint of Scholastic Inc., 2023)
Introduces young readers to how slow or fast different mammals move, and covers what they eat, where they live, and more.
Meet the mammals -- #10 slowest mammal: three-toed sloth -- Three-toed sloth close-up -- #9: squirrel -- #8: hippopotamus -- #7: sea lion -- #6: Dall's porpoise -- #5: lion -- #4: greyhound -- #3: pronghorn -- #2: cheetah -- #1 fastest mammal: Mexican free-tailed bat -- Mexican free-tailed bat close up -- Mammals fast and slow.
Includes index.
3.7
K-3
800L
Keywords: Mammals -- Miscellanea -- Juvenile literature; Mammals -- Locomotion -- Juvenile literature; Mammals -- Miscellanea; Mammals -- Locomotion; Mammals